Assessment of depression symptoms in female cancer patients: focus on concurrent validity : Depression in female cancer - Miraglia Raineri, Alessandra; Lauro Grotto, Rosapia (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The present research explores Concurrent Validity of two depression measures the Beck Depression Inventory (BDI) and the Depression Subscale of the Hospital Anxiety and Depression Scale (HADS- Depression subscale) in specific oncological groups (female cancer and onco-hematological patients). Method: A correlational study was designed and took place at Careggi Universitary Hospital in Florence, including 339 oncological patients, in particular 103 (59 Women and 44 men) patients suffering from lymphoma, and 236 patients suffering from female cancer. We estimated, by Pearson’s r, Concurrent Validity between BDI and HADS depression’s subscale. Results: Correlations failed to reach the 0.55 cut-off in the female cancer group (r=.34, p